Hubungan Kepemimpinan Kepala Sekolah dan Motivasi Kerja dengan Kedisiplinan Guru SD Gugus I Kecamatan Sibulue Kabupaten Bone - Nirmala; Arismunandar; Muhammad Irfan (PT PUSTAKA CENDEKIA GROUP, 2025)
This study is a quantitative study with a correlational design that aims to determine whether or not there is a Relationship between Principal Leadership and Work Motivation with Teacher Discipline of Elementary School Cluster 1, Sibulue District, Bone Regency. The population in this study were teachers of Elementary School Cluster 1, Sibulue District, Bone Regency, while the sample in this study was 30 teachers, namely elementary school teachers in Cluster 1, Sibulue District, Bone Regency. Data collection was carried out by providing questionnaires and documentation. The findings obtained, the principal's leadership with an average of 99.10 and a percentage of 79.28%% is classified as good, work motivation with an average of 136.47 and a percentage of 89.78% is classified as very good, and teacher discipline with an average of 119.83 and a percentage of 79.88% is classified as very good. The results of this study also show that the t-value (X1 = 2.814, X2 = 4.019) is greater (≥) the t-table value (1.703) at a significance level of 5%. Thus, H0 is rejected and H1 is accepted. The results of the study concluded that there is a significant relationship between principal leadership and work motivation with teacher discipline at Elementary School Gugus 1, Sibulue District, Bone Regency.